2020
DOI: 10.4062/biomolther.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Selonsertib Inhibits Liver Fibrosis via Downregulation of ASK1/ MAPK Pathway of Hepatic Stellate Cells

Abstract: Liver fibrosis constitutes a significant health problem worldwide due to its rapidly increasing prevalence and the absence of specific and effective treatments. Growing evidence suggests that apoptosis-signal regulating kinase 1 (ASK1) is activated in oxidative stress, which causes hepatic inflammation and apoptosis, leading to liver fibrogenesis through a mitogen-activated protein kinase (MAPK) downstream signals. In this study, we investigated whether selonsertib, a selective inhibitor of ASK1, shows therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Our work showed Ser could significantly block the activation of ASK1/P38/JNK and NFκB signal pathways induced by IL-1β in rat chondrocytes. The observations partly mimic results of Yoon et al study, which demonstrated that selonsertib alleviates liver fibrosis via blocking ASK1/MAPK pathway in hepatic stellate cells ( Yoon et al, 2020 ). Collectively, the two pathways were involved in the protective roles of Ser in OA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our work showed Ser could significantly block the activation of ASK1/P38/JNK and NFκB signal pathways induced by IL-1β in rat chondrocytes. The observations partly mimic results of Yoon et al study, which demonstrated that selonsertib alleviates liver fibrosis via blocking ASK1/MAPK pathway in hepatic stellate cells ( Yoon et al, 2020 ). Collectively, the two pathways were involved in the protective roles of Ser in OA.…”
Section: Discussionsupporting
confidence: 85%
“…However, the detailed role of Ser in OA treatment remains to explore. Previous study reported that Ser could block ASK1/MAPK pathway in hepatic stellate cells and down-regulate ASK1-JNK-DRP1 pathway in macrophage, suggesting the possible mechanism of its action ( Yoon et al, 2020 ; Lou et al, 2021 ). In this study, we aim to elucidate the therapeutic effects and molecular mechanisms of Ser in OA.…”
Section: Introductionmentioning
confidence: 98%
“…In this direction, selonsertib, an apoptosis signal-regulating kinase 1 (ASK1) inhibitor, was proposed. In fact, selonsertib demonstrated potent antifibrotic activity in rodent models (64,65). However, two large phase 3 trials in NASH patients with either advanced fibrosis or cirrhosis failed, as selonsertib did not improve liver fibrosis after 48 weeks of therapy compared to placebo (66).…”
Section: Disconnecting Nafld From Inflammation And/or Fibrosismentioning
confidence: 99%
“…ASK1, which is activated by a variety of pro-fibrotic factors, activates MAPK signal pathway, and participates in hepatocyte apoptosis, inflammation and fibrosis. Selonsertib (GS-4997), a selective ASK1 inhibitor, inhibited HSCs proliferation and ECM production by blocking the ASK1/MAPK pathway, and significantly alleviated DMN-induced liver fibrosis in rats ( Yoon et al, 2020 ). Selonsertib was used to treat 74 NASH patients with F2–F3 fibrosis for 24 weeks with dose of 6 mg/d or 18 mg/d in a multicenter phase II clinical trial.…”
Section: Progress In the Treatment Of Liver Fibrosismentioning
confidence: 99%